Development and its Actors: The Milieu of Islamic-based Development - Shereeza binti Mohamed Saniff (IJUS | International Journal of Umranic Studies, 2022)
This article looks at the evolution of Islamic-based development as a field of study and then examines the concept of Islamic-based development actor (or IbD Actor). The emphasis of this article is on the importance of humans as the actors of development. It is the humans, as the central figure that defines which development paradigm is to transpire as development occurs at the hands of humans. However the differing development paradigms between the Islamic-based to that of conventional strike at the very core – the philosophical underpinnings. The conventional development paradigm influences even the Muslim countries. The dominance of conventional development has even overshadowed the concept of Islamic economics, one facet of Islamic development. With such antagonism natural conflict arises. This results in the achievement of the ultimate goals of the development paradigms to differ completely. Hence the dilemma to man as the actor of any development process who need to decide which development goal that is needed to be achieved foremost. In seeking out the required answers for this article, library research is mainly used to obtain the various concepts and assessment applied to in this article with textual analysis carried out. The article suggests that for man as actor of development to be detangled from the dilemma, only a truly Islamic-based development paradigm can be seen as the saviour. However for a truly Islamic-based development to transpire requires foremost man to be the IbD Actor.